Laser induced crystallization of Co–Fe–B films - Maria Almeida (Nature Portfolio, 2021)
Abstract Local crystallization of ferromagnetic layers is crucial in the successful realization of miniaturized tunneling magnetoresistance (TMR) devices. In the case of Co–Fe–B TMR devices, used most successfully so far in applications and devices, Co–Fe–B layers are initially deposited in an amorphous state and annealed post-deposition to induce crystallization in Co–Fe, thereby increasing the device performance. In this work, first direct proof of locally triggered crystallization of 10 nm thick Co–Fe–B films by laser irradiation is provided by means of X-ray diffraction (XRD) using synchrotron radiation. A comparison with furnace annealing is performed for benchmarking purposes, covering different annealing parameters, including temperature and duration in the case of furnace annealing, as well as laser intensity and scanning speed for the laser annealing. Films of Co–Fe–B with different stoichiometry sandwiched between a Ru and a Ta or MgO layer were systematically assessed by XRD and SQUID magnetometry in order to elucidate the crystallization mechanisms. The transformation of Co–Fe–B films from amorphous to crystalline is revealed by the presence of pronounced CoFe(110) and/or CoFe(200) reflexes in the XRD θ-2θ scans, depending on the capping layer. For a certain window of parameters, comparable crystallization yields are obtained with furnace and laser annealing. Samples with an MgO capping layer required a slightly lower laser intensity to achieve equivalent Co–Fe crystallization yields, highlighting the potential of laser annealing to locally enhance the TMR ratio.